Characteristics of magnesium rich synthetic gypsum and its effect as a secondary nutrient source for rubber seedlings on acid soils - Ayanda, Arolu Fatai (2021)
Ultisols and Oxisols, the common soil in Malaysia, do not usually contain optimal levels of cations such as K, Ca and Mg, required in large amounts for crop growth and productivity. Thus, the management of input plays an important role in crop production in these widely occurring soils of Peninsular Malaysia. Rubber requires large amounts of nutrients to sustain its growth and production so that faster growth and high latex yield can be achieved and maintained. The use of fertilizer to supply nutrients for rubber is essential in rubber cultivation; however, fertilizer costs account for a larger percentage of production costs. As such, it is imperative to seek for a local alternative source that is cost-effective. Recent studies on MRSG, a by-product obtained from industrial refining of rare earth show that the material contains nutrient elements that may be beneficial for rubber growth in addition to its high pH that ameliorate the impact of soil acidity limitation on crop growth. Therefore, this research was conducted to study the physicochemical characteristics of MRSG, its effect on acid soils, rubber growth, and whether MRSG can be a secondary nutrient source for rubber plants at the growing phase. The characterization results indicated that MRSG has valuable properties that can promote its use in amending soil fertility constraints on nutrient-deficient tropical acid soils. Incubation and leaching column studies were conducted to assess the effect of MRSG on the chemical properties of Ultisol and Oxisol in Malaysia and model the nutrient release pattern from the material over a 6-month period. The incubation experiment was as a factorial experiment consisting of 2 soil types, 3 treatments and five rates including control (0, 1, 2, 4 and 8) and laid out as a completely randomized design (CRD). For the leaching experiment, the treatment consists of 1 t ha-1 of MRSG, GML and kieserite with three replications arranged in a complete randomized design (CRD). The study comprised two soil orders viz Ultisol and Oxisol belonging to the Bungor and Segamat series based on Malaysian classification for local soils. The amount of nutrients released into soil solution and present on the soil exchange site due to the application of MRSG at various rates and months were fitted into different functions using python programming script. The pattern of nutrient release from MRSG was similar in the two studied soils and amounts of nutrient released increased with the duration of the experiment. Nutrients release kinetics for all samples are adequately described by the parabolic diffusion, power function and Elovich equations. The intercept constants of the equations are strongly positively related to the ratio of nutrients contained in MRSG. The models showed good performance (R2 value in range 0.9 to 0.99) in most samples tested except for the kieserite treatment group. The model indicates that MRSG has a disintegration behavior similar to GML and can be used to achieve a similar result in acid soil amelioration and soil nutrient enhancement. The leaching study showed that MRSG is available in the soil system and can move beyond the zone of incorporation into the sub-soil to further ameliorate subsoil acidity. The Ca and Mg ions contained in MRSG are not easily leached out of the soil profile, thus MRSG can be a potential substitute for lime (GML) on acid soils. For nursery trial to understand the effect of MRSG application on the growth of immature rubber, three-month-old rubber seedlings of the same size and/or height were obtained from RISDA for planting on Ultisol and Oxisol. The experimental units consisted of four rubber seedlings, with a total of 200 seedlings planted in the polybags. Treatments for this study was based on using GML, kieserite and MRSG as fertilizer source to supply the recommended Mg requirement for rubber seedlings in the nursery based on RISDA formulation. Determination of growth parameters of the rubber seedlings was carried out at 3 monthly intervals. The result of the experiment showed that incorporation of MRSG increased the soil pH and decreased the aluminum content. MRSG application also increased the level of available phosphorus and secondary nutrients such as calcium. The growth of rubber seedlings in the glasshouse for the parameters of height, stem diameter, root length and root surface area were significantly enhanced in the two studied soils (Ultisol and Oxisol) by the addition of MRSG which gave a result comparable to other sources of Mg fertilizer. It was observed that plant growth performance was better on the Ultisol compared to the Oxisol. This study showed that the logistic growth curve model in the form of y = A/ (1+be-ct), where y and t were the plant growth parameters and months after transplanting, respectively, while A, b and c were regression constants were biologically fitted in describing the growth in terms of each of the parameters (plant height, stem girth and total plant biomass) versus months after transplanting. At each treatment, the model had an F value with a high approximate probability level at a = 0.0001. In terms of the vegetative growth of the rubber seedlings, MRSG treatments gave comparable results to that of GML and kieserite, thus, indicating the possibility of using MRSG as a replacement of kieserite and GML as Mg source (Mg-fertilizer) to sustain rubber seedling growth.